Millennial consumers' responses to cause-related marketing in support of LGBTQ homeless youth - Hensley, Cammie, author; Diddi, Sonali, author; Hyllegard, Karen, author; MDPI, publisher (Colorado State University. Libraries, 2019)
This study explored Millennial consumers' responses to a cause-related marketing (CRM) initiative for a sensitive social cause—lesbian, gay, bisexual, transgender and queer (LGBTQ) homeless youth. Qualitative and quantitative research methods were employed to examine the effctiveness of CRM in generating financial support for LGBTQ homeless youth. Findings revealed that self-cause congruence may be an important factor in determining Millennial consumers' responses to a CRM initiative for LGBTQ homeless youth; whereas, message frame/appeal may be less important for generating response to such an initiative. Findings also indicated that gender, information processing, guilt, and skepticism influenced Millennial consumers' attitudes toward brand, attitudes toward cause, and behavioral intentions toward the CRM initiative. These findings offer implications for brands/companies that may wish to engage in CRM initiative in support of sensitive social causes. By addressing a sensitive social cause-LGBTQ homeless youth-findings provide an original contribution to the CRM literature. Findings reveal that self-cause congruence is an important predictor of behavioral intention toward the LGBTQ social cause. This provides an implication for marketers who want to target their relationship-building efforts toward individuals who have demonstrated prior engagement with a social cause. Findings also have implications for brands/companies that wish to develop CRM initiatives for controversial causes.
Keywords: cause-related marketing; information processing; LGBTQ homeless youth; message framing; self-schema; skepticism